(5x-15)*5x-15=0

Simple and best practice solution for (5x-15)*5x-15=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x-15)*5x-15=0 equation:



(5x-15)*5x-15=0
We multiply parentheses
25x^2-75x-15=0
a = 25; b = -75; c = -15;
Δ = b2-4ac
Δ = -752-4·25·(-15)
Δ = 7125
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{7125}=\sqrt{25*285}=\sqrt{25}*\sqrt{285}=5\sqrt{285}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-75)-5\sqrt{285}}{2*25}=\frac{75-5\sqrt{285}}{50} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-75)+5\sqrt{285}}{2*25}=\frac{75+5\sqrt{285}}{50} $

See similar equations:

| -7u+3(u-7)=-5 | | Z6-2z3-3=0 | | 3(2x+6)=2(5x+2) | | (5x-15)=0 | | x3-81=0 | | 11b-3b-4b=8 | | 24x+24=21x+63 | | n2−2=1 | | 3-(x-12)=35 | | X/3-x=-2 | | .7(3)+.5y=5.75y | | 19d-3d+4d-14d+3d=9 | | -6(b+92)=24 | | n2− 2=1 | | 5x−3(x−2)=10+x | | f/4+-8=-11 | | 5u-45=-3(u-9) | | 12=2m+5 | | 2(f-42)=76 | | 3^x+4^x=9^x | | 6x1=5x1+10 | | 3(x+2-1)=2(x-1+4) | | d/3-6=-5 | | 19s-14s=15 | | 12x+5=5+13x | | 5z+15=3(z+1) | | 288=54x+18 | | 4=-2+-c | | 2^x^+^16=32^x | | 3x-3=x−19 | | 5x-7=(3x+1) | | 12.6y+8=10.2y+4.4 |

Equations solver categories